AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING PROCEDURAL TEXT AT THE ELEVENTH GRADE OF SMA NEGERI 2 HILISALAWA’AHE - Soguines Putri Halawa (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
The purpose of this research is to describe students’ ability in writing procedural text and find out the obstacles students experienced in writing procedural text. This research used qualitative research. The data were taken from 18 procedural text that made by students. The data source was eleventh students at SMA Negeri 2 Hilisalawa’ahe Academic Year 2023/2024. The techniques of data collection were writing test and interview. The result of the research was the students’ ability in writing procedural text varied at every aspect of writing. However, the average students’ ability is content aspect was 20.27 which categorized fair to poor level, organization aspect was 13.5 which categorized fair to poor level, vocabulary aspect was 11.38 which categorized fair to poor level, language use aspect was 10.83 which categorized very poor level, and mechanic aspect was 4.3 which categorized fair to poor level. This is demonstrated based on the students’ level of difficulty in writing procedural text. And the result of data analysis of students’ ability in writing procedural text at the eleventh grade of SMA Negeri 2 Hilisalawa’ahe was categorized in poor. Furthermore the obstacles experienced by students in writing procedural text were difficulties in organizing in ideas, limited vocabulary and incompetence at grammar. It is suggest to the English teacher improve learning in the classroom, especially in procedural text material.